INNOVATIVE SOLUTIONS IN ARCHITECTURE: 3D PRINTING AS A TOOL FOR OPERATIONAL CONSTRUCTION IN WARTIME - Krasniy, Eduard (Theory and practice of design, 2025)
The purpose of the study is to identify the prospects and limitations of using 3D printing technology for the rapid construction of architectural objects in wartime conditions and to outline the possibilities for its implementation in Ukrainian practice. The research methodology is based on a comprehensive approach that combines analysis of current scientific literature, study of international experience in the application of 3D printing in architecture, expert assessments of technological capabilities and materials, as well as analysis of the prospects and limitations of implementing this technology in wartime conditions in Ukraine. The use of comparative and systematic analysis made it possible to identify the key factors in the effectiveness of 3D printing for rapid construction, as well as to outline ways of integrating this technology into Ukrainian architectural practice. Results. 3D printing technology in architecture is considered one of the most promising innovations capable of ensuring a rapid response in crisis situations. Its application allows minimizing the expenditure of time, resources, and human labor, which is especially important in wartime, when there is an urgent need to create protective structures, medical centers, residential modules, and other critical infrastructure facilities. The article discusses the current state of development of 3D printing technologies in architecture, their technical capabilities, and examples of their use around the world. Particular attention is paid to the potential of this technology for Ukraine, in particular in the process of rapid construction of civil protection facilities, shelters, and temporary living spaces. The advantages of 3D printing are analyzed–high speed of construction, material savings, environmental friendliness, adaptability of design solutions–as well as limitations: regulatory barriers, equipment cost, and material durability. The scientific novelty of the article lies in a comprehensive study of the possibilities of using 3D printing specifically in the context of the military conflict in Ukraine, which allows assessing its potential for the rapid restoration of residential and social infrastructure. For the first time, the advantages, limitations, and technological aspects of 3D printing in crisis situations have been systematically analyzed, with practical recommendations for its implementation in Ukrainian construction practice. Practical relevance. The results of this study can become an important element in increasing the stability and security of the state in wartime and post-war conditions, forming a new paradigm of construction focused on speed, flexibility, and innovation.